Effects of Repolishing Systems on Surface Characteristics of a 3D-Printed Permanent Material - Alessandro Vichi; Giovanni Mura; Federico Vannini; Sofia Baldani; Gaetano Paolone; Cecilia Goracci (Applied Sciences)
Background: 3D-printed (3DP) resins for permanent restorations are increasing in availability and gaining popularity. Aesthetic stability is an issue of dental resins that may compromise the long-term success of restorations. A staining test has been performed to evaluate gloss, roughness, and color staining of a permanent 3DP resin, and the effects of repolishing. Methods: Squared specimens of one 3DP permanent resin (Crown permanent, Formlabs) have been CAD-designed and 3D-printed. After the roughness, gloss, and color measurements, they were immersed in a coffee staining bath at 44 °C for 24 h and then measured again. Subsequently, they were repolished with three different systems: prophy cup and Nupro prophy paste, HiLuster Plus 2-step, and Opti1Step Polisher 1-step polishing systems. Results: Gloss and Roughness were not significantly affected by the staining procedure. No significant changes were observed for gloss after repolishing, while one of the tested systems (prophy cup and paste) produced a worsening effect on roughness. Color was affected by the staining procedure. After repolishing, b* changes were almost completely recovered, while L* changes were recovered only partially. Conclusions: Color stability still represents a challenge, and 3DP resins for permanent use are affected. Repolishing systems should be further developed and tested.